The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4102/ajlm.v10i1.1408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on blood donation and supply in Africa

Abstract: No abstract available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Replacement donations thus remained the only feasible solution to severe blood shortages being faced by the country and the need to meet the increased demand for blood due to haemolytic episodes, road traffic accidents, surgical interventions, maternal comorbidities, severe anaemia, haemorrhagic shocks, cancer related issues and other medical conditions. Study showed the need to address the protracted issue of COVID-19 pandemic holistically with considerations to its negative impacts on blood and blood products availability and supply [27,29]. Another study by Okoroiwu et al (2018) on voluntary donations during COVID-19 pandemic in Nigeria showed similar trend of negative impacts [31].…”
Section: Discussionmentioning
confidence: 98%
“…Replacement donations thus remained the only feasible solution to severe blood shortages being faced by the country and the need to meet the increased demand for blood due to haemolytic episodes, road traffic accidents, surgical interventions, maternal comorbidities, severe anaemia, haemorrhagic shocks, cancer related issues and other medical conditions. Study showed the need to address the protracted issue of COVID-19 pandemic holistically with considerations to its negative impacts on blood and blood products availability and supply [27,29]. Another study by Okoroiwu et al (2018) on voluntary donations during COVID-19 pandemic in Nigeria showed similar trend of negative impacts [31].…”
Section: Discussionmentioning
confidence: 98%
“…Blood supply in Botswana has been in chronic shortage for years and suffered an acute crisis in 2020 [10]. In 2021, Author co-conducted workshops with Gaborone city residents, entrepreneurs from a local incubator, and National Blood Transfusion Services (NBTS) staff to understand the reasons behind the chronic blood shortage [9].…”
Section: Blood Supply In Botswanamentioning
confidence: 99%